Adjunctive intrauterine Foley’s Catheter Balloon adding to hypogastric artery ligation in the conservative management of morbid adherent placenta previa - Sallam, Hany F.; Shady, Nahla W. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Objective of present study was to demonstrate the efficacy of Foley’s catheters balloon tamponade as an adjuvant to control blood loss during and after a caesarian section in patient undergone hypogastric artery ligation (HAL) due to morbid adherent placenta previa (MAPP). Methods: A single-center retrospective case-control clinical trial was carried out in a tertiary university hospital between March 2015 and March 2018, 124 women were undergoing cesarean delivery for MAPP, were managed conservatively either with HAL or HAL plus inflated Intrauterine Foley’s Catheter Balloon to control post-partum hemorrhage secondary to MAPP. In the case of conservative treatment protocol failure, cesarean hysterectomy was performed. Results: 124 women were enrolled (n=62 in each group). group of women received HAL plus Intrauterine Foley’s Catheter Balloon (group II)) showed a significant reduction in intraoperative and 4 hours post-operative blood loss compared with (Group I) which received HAL without Intrauterine Foley’s Catheter Balloon. (P = 0.0001,0.0.015), so the overall estimated blood loss in group II showed significant reduction compared with group I (P = 0.0001). Conclusions: Adjunctive intrauterine Foley's catheter balloon adding to HAL ligation in the management of MAPP is a novel combination approach have proved to be effective to control of intraoperative and PPH and to preserve the uterus as possible and change in the concept of MAPP management always mandates hysterectomy. And may become an alternative valid option to planned cesarean-hysterectomy in well-selected cases who have a strong desire for future fertility.